Factors Contributing to the Successful Implementation of an OHS Management System in the Informal/SME Sector - Ria Novasari Mei Astuti; Doni Hikmat Ramdhan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
The informal sector/SMEs (Small and Medium Enterprises) play a significant role in Indonesia's economy. However, this sector often faces various occupational safety and health (OSH) risks. An OSH management system can help SMEs manage OSH risks and improve their business performance. This study aims to examine the factors that contribute to the successful implementation of occupational safety and health (OSH) management systems in the informal sector/SMEs (Small and Medium Enterprises). The study employs a systematic literature review methodology following PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis). The study was conducted in April 2024, searching for relevant articles from reputable sources such as Google Scholar, ProQuest, and ScienceDirect. The review encompassed 16 relevant articles and revealed that the factors contributing to the successful implementation of OSH programs can be categorized into two main factors: external and internal factors. External factors play a crucial role in enabling the successful implementation of OSH management systems in the informal sector/SMEs. These factors encompass the supportive roles of government, the private sector, and various organizations. This study on successful OSH management system implementation in the informal sector/SMEs highlights key factors for policymakers, practitioners, and researchers. Policymakers can support implementation through financial aid and clear regulations. Practitioners should consider these factors when assisting SMEs, tailoring strategies for each business. Researchers can contribute by developing more.